Analisis Kebijakan Pendidikan: Kajian Atas Persepsi Kepala Sekolah, Guru, Dan Siswa Smp Negeri Se-Kecamatan Kedungwuni Kabupaten Pekalongan Tentang Penerapan Sistem Zonasi - Nelli Murodah; Dian Nur Muniroh (LPPM IAIN Sorong, 2022)
Abstract: This research is a qualitative research that aims to analyze the perceptions of school principals, teachers, and students of public junior high schools in Kedungwuni District, Pekalongan Regency regarding the implementation of the zoning system. Data were collected by in-depth interviews, participatory observation, and documentation studies. Data analysis used an interactive analysis model proposed by Miles and Huberman. The results show that the perceptions of school principals, teachers, and students of public junior high schools in the Kedungwuni District, Pekalongan Regency, regarding the implementation of the zoning system differ. There are those who see it from a positive perspective, there are also negative ones. There are those who agree with the implementation of this system, some are not. There are those who feel benefited, but there are also views that are disadvantaged. But whatever it is, in a policy it is natural if there are pros and cons. For this reason, it is necessary to have an in-depth understanding and continuous outreach by various parties regarding this policy.